2012
DOI: 10.1111/j.1469-0691.2012.03773.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of Escherichia coli susceptibility in strains causing asymptomatic bacteriuria for women with recurrent symptomatic urinary tract infections receiving prophylaxis

Abstract: A significant proportion of women develop a recurrence following an initial urinary tract infection (UTI). In women with recurrent UTI, the predictive value of asymptomatic bacteriuria (ASB) for the development of a subsequent UTI has not yet been established and it is not known whether information from an asymptomatic sample is useful in guiding antimicrobial therapy. To address these questions, we used data that originated from the 'Non-antibiotic prophylaxis for recurrent urinary tract infections' (NAPRUTI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…However, we have recently shown that asymptomatic E. coli strains are predictive for strains that cause a symptomatic E. coli UTI in women with rUTI [15].…”
Section: Discussionmentioning
confidence: 91%
“…However, we have recently shown that asymptomatic E. coli strains are predictive for strains that cause a symptomatic E. coli UTI in women with rUTI [15].…”
Section: Discussionmentioning
confidence: 91%
“…However, the susceptibility and pulsed-field gel electrophoresis pattern of E. coli strains isolated from urine in the month before a symptomatic E. coli UTI were similar in about three quarter of patients. These findings suggest an intracellular bacterial reservoir could possibly serve as a nidus for recurrence in same-strain UTIs in women with recurrent UTIs [ 14 ].…”
Section: Pathogenesis Of Utismentioning
confidence: 99%
“…In six studies of women experiencing RUTI following a primary infection, the rate reinfection by primary strain varied from 47% to 81%. 4045 Although five of the six studies propose a slightly higher rate of reinfection by QIR recurrence (> 50% reinfection by primary strain), 4145 the aggregated results suggest that both ascending reinfection and QIR recurrence are significant causes of RUTI in women (Table 1). …”
Section: Etiologymentioning
confidence: 99%